Produção de hidrogênio através da reforma a vapor de etanol com captura de dióxido de carbono usando catalisadores bifuncionais à base de níquel e óxido de cálcio dopados com magnésio e alumínio - Oliveira, Cassiano Cunha (2021)
This work evaluated the performance of nickel-based catalysts supported on CaO and CaO-MgO-Al2O3 in the sorption enhanced steam reforming of ethanol (SESRE) aiming the production of high purity H2. The catalysts were prepared by sol-gel method and characterized by different methods: Temperature programmed reduction (TPR), X-ray diffraction (XRD), scanning electronic microscopy (SEM) with chemical element mapping, N2 physisorption and thermogravimetric analysis (TGA). XRD analyses showed that the predominant phases were CaO, MgO, CaCO3, Ca(OH)2 and NiO in the calcined samples and Ni0 in the reduced and passivated samples. TPR profiles indicated that all catalysts presented a high degree of reduction (Ni/CaMgAl-68 > Ni/CaMgAl-79 > Ni/Ca), although the Ni/CaMgAl-X samples presented high reduction temperatures indicating the formation of NiAl2O4. TPR performed under temperature conditions of catalyst activation obtained a degree of reduction of NiO over 90% due to the contact of the samples in a reducing atmosphere for a longer time than that used during TPR analysis. TGA showed that the catalyst Ni/CaMgAl-68 was the most stable during the 20 cycles of carbonation and decarbonation because it had the lowest loss of CO2 uptake capacity. However, Ni/CaMgAl-79 catalyst showed the highest capture capacity after 20 cycles in relation both to mass of catalyst and by mass of CaO. The catalytic tests in the SESRE showed that Ni/CaMgAl-79 catalyst had the best performance since it had the longest high purity hydrogen production time. In the pre-breakthrough period, the H2 mole fractions were close to 90% for all samples during all reaction cycles. Furthermore, the CO2 capture promoted by the sorbent allowed these concentration values to be higher than conventional steam reforming of ethanol, due to the equilibrium shift that favors H2 production. The TGA performed after the reaction cycles also showed that probably the presence of the metal oxides (MgO and Al2O3) in the catalysts minimized the formation of coke on the surface of the catalysts, obtaining average deposition rates of 11.5, 7.4 and 6.2 mgC/gcat/h, for the Ni/Ca, Ni/CaMgAl-79 and Ni/CaMgAl-68 catalysts, respectively.